The Impact Of Floods And Torrents On Water Facilities And Installations In The Green Mountain Region - Mahmoud Al-Siddiq Al-Tawati; Abdul Raouf Al-Tashani (Journal of Pure & Applied Sciences, 2025)
This research deals with the impact of torrential rains and devastating floods after the Mediterranean storm Daniel on water installations in the Green Mountain region, the study included water dams, stone and box obstruction dams, as well as ferries spread in Jabal Al-Khader within an area of 3127 km2, collected data and information measurement and field documentation and from topographic maps and satellite images before and after the disaster, the study aims to know the places of facilities affected by the impact of floods and floods in the region, and assess the impact on those facilities from the impact of floods during Previous periods, the quantitative approach and the descriptive approach were used in the study with the help of a modern program in geographic information systems Arcmap 10.3 GIS and remote sensing techniques, GPS and computer programs for analysis and interpretation of the moformer properties of water installations basins, and the study found that the water installations were not subject to periodic maintenance, and they were not chosen appropriate places for dams Some ferries were not designed according to the quantities of water discharge of the valleys, the most important dams and ferries were documented in the study area, the study recommends the importance of facility management Aquatic.